Clinical Legal Education in Nigeria: Envisioning the Future - Oludayo Bamgbose (Bond University, 2021)
Clinical Legal Education (CLE) as an educational initiative is designed to allow law schools to meet emerging practice-based needs which the traditional legal education framework fails to address. Although CLE only started in the early 1970s in Africa, it has become widely implemented across law institutions in Africa, following European and American examples. CLE in Africa started in South Africa; where, prior to 1972 there were no formal CLE programs as South African law schools mainly focused on private law rather than public law. Another factor affecting the uptake of CLE was that law school courses were generally offered on a part-time basis, which implied that law students could be engaged in personal activities that prevented them from involvement in other important law school-related programs. The discriminatory nature of the law during the South African apartheid regime also impeded access to justice in poor communities. In light of this developing need, the South African CLE program began informally at the University of Witwatersrand, Johannesburg, and formally at the University of Cape Town, in the early 1970s. A 1973 Ford Foundation-sponsored event gave the impetus needed to begin the establishment of law clinics across other institutions in South Africa. Within the Nigerian context, CLE was officially launched in 2005 with four pilot clinics. Today, many Nigerian law faculties and the Nigerian law school campuses now have law clinics in their respective institutions due to the advantages associated with their adoption in the contemporary era. With Nigeria's exit from the military regime only five years earlier, CLE was embraced by some law faculties because of its potential to increase democratic practices among the people, foster access to justice , and improve the quality of legal scholarships available to law students. Fifteen years after the launch of CLE in Nigeria, it is now essential to take stock, to ascertain if the program is still on course and to consider what the future may hold. It is against this background that this article is structured in three segments: firstly, examining the Nigerian CLE journey to date; secondly, considering future developments; and lastly, concluding with recommendations.